2023
DOI: 10.1101/2023.03.10.531533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrapotent SARS coronavirus-neutralizing single-domain antibodies that bind a conserved membrane proximal epitope of the spike

Abstract: Currently circulating SARS-CoV-2 variants have gained complete or significant resistance to all SARS-CoV-2-neutralizing antibodies that have been used in the clinic. Such antibodies can prevent severe disease in SARS-CoV-2 exposed patients for whom vaccines may not provide optimal protection. Here, we describe single-domain antibodies (VHHs), also known as nanobodies, that can broadly neutralize SARS-CoV-2 with unusually high potency. Structural analysis revealed their binding to a unique, highly conserved, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Of note is mAb C1717, which targets the viral membrane proximal side of the NTD and SD2 domain and has been found to potently neutralize BQ and XBB variants in pseudo-particle assays (19,57). Furthermore, nanobodies targeting the highly conserved quaternary epitope in the S2 subunit of the spike have also been found to potently inhibit BQ and XBB Omicron sub-lineages (71). The discovery and development of mAbs targeting conserved non-RBD regions will provide new treatment and prevention options for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note is mAb C1717, which targets the viral membrane proximal side of the NTD and SD2 domain and has been found to potently neutralize BQ and XBB variants in pseudo-particle assays (19,57). Furthermore, nanobodies targeting the highly conserved quaternary epitope in the S2 subunit of the spike have also been found to potently inhibit BQ and XBB Omicron sub-lineages (71). The discovery and development of mAbs targeting conserved non-RBD regions will provide new treatment and prevention options for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy (IGHV1-58) and light chain (IGKV3- Although HuMab K501SP6 is promising for its broad neutralization and genetic uniqueness, we did not determine where on the spike protein HuMab K501SP6 bound. Limited studies have found potent neutralizing mAbs that target non-RBD epitopes and successfully neutralize all Omicron sub-lineages (19,57,71). Of note is mAb C1717, which targets the viral membrane proximal side of the NTD and SD2 domain and has been found to potently neutralize BQ and XBB variants in pseudo-particle assays (19,57).…”
Section: Discussionmentioning
confidence: 99%
“…116 Recent preprint reports an extremely potent antibody targeting a quaternary epitope between the N1194 glycan and the membrane. 119 The TMD seems to be important during the initialization of the fusion process. 120,121 The TMD features a number of conserved cysteines grouped in four clusters.…”
Section: S2mentioning
confidence: 99%
“…While many therapeutic mAbs target virus binding to host cells, fusion-blocking mAbs have also been described (50, 66,84,[169][170][171][172][173]. Broadly neutralizing antibodies have also been identified that target MPERs including ones against HIV Env (174,175), filovirus GPs (176), influenza HA (177), and SARS-CoV-2 (178). MPER-targeting mAbs restrict flexibility, limiting the range of motion of fusion protein ectodomains (84,175).…”
Section: Therapeutic Restriction Of Viral Fusionmentioning
confidence: 99%